Intermediate wheatgrass (Thinopyrum intermedium) and grain sorghum as novel, sustainable ingredients in extruded precooked pasta and expanded snacks – Life cycle assessment, physicochemical properties and product quality - Rivera, Julia (My University, 2025)
This thesis explores the potential of Intermediate Wheatgrass (IWG) and sorghum as sustainable alternatives to conventional grains in the production of extruded precooked pasta and expanded snacks, while evaluating their environmental impacts through a life cycle assessment (LCA). IWG, with its deep root system, enhances soil health and carbon sequestration, addressing challenges like soil erosion and high water usage. Sorghum offers sustainability benefits in water-scarce regions, with comparable or improved product performance. Six pasta formulations incorporating wheat, IWG, and sorghum were assessed for functionality and cooking performance. Pasta made solely from wheat exhibited the highest cooking loss at 5.6%, while IWG pasta had 3.9%, and sorghum pasta achieved the lowest cooking loss at 1.9%. RVA analysis revealed wheat’s higher peak viscosity (1064 cP) compared to sorghum (979 cP) and IWG (443 cP), suggesting differences in starch binding and degradation that influenced cooking outcomes. The study also examined the properties of IWG and sorghum in expanded snack production. IWG snacks exhibited the highest density at 0.28 g/cm³ compared to corn (0.12 g/cm³) and sorghum (0.14 g/cm³), indicating potential differences in textural outcomes. Expansion ratios revealed that sorghum achieved 10.22, significantly higher than IWG's 5.80, while corn reached 10.58. In terms of hardness, IWG snacks measured 22.95 kg, notably harder than corn (15.54 kg) and sorghum (12.96 kg). These findings highlight opportunities to balance texture and sustainability in snack formulations. LCA results showed sorghum with the lowest Global Warming Potential (GWP) at 0.09 kg CO2 eq/kg for snacks and 0.11 kg CO2 eq/kg for pasta. IWG exhibited higher direct GWP (0.31 kg CO2 eq/kg for pasta) but transformed into a carbon sink when considering carbon sequestration and straw allocation, reducing net GWP to -0.7 kg CO2 eq/kg. These findings underscore IWG’s potential to offset emissions through soil organic carbon sequestration (42 tons C/hectare), while sorghum offers low emissions with favorable product properties. This research highlights the environmental and functional advantages of integrating IWG and sorghum into food systems, contributing to more sustainable agricultural practices and product development.
Keywords: Kernza; Sustainability; LCA; Pasta; Extrusion